Materials Nanoarchitectonics for Advanced Physics Research - Katsuhiko Ariga (Advanced Physics Research, 2023)
Abstract Nanoarchitectonics combines nanotechnology with existing fields such as organic chemistry, supramolecular chemistry, materials science, microfabrication, and bio‐chemistry. It is a concept to create the architecture of atoms, molecules, nanomaterials, and other units for use in functional material systems through various processes. Structural control through nanoarchitectonics can contribute to a variety of fields for advanced physical research. New physical properties can be controlled by forming atomic arrangements, molecular designs, polymer syntheses, crystal structures, self‐assembled structures, and superstructures. Construction of nanospace structures can also elucidate the specific physical properties of molecules trapped in them. Thus, nanoarchitectonics has great potential to contribute to advanced physical research. This paper will discuss some perspectives, categorizing the examples into those that focus on structure formation, those related to optical and photonic functions, those that exploit electronic and electrical properties, and those oriented toward device applications. The presented examples ensure significant contribution of nanoarchitectonics to advanced physical research.